DGN-Handlungsempfehlung (S1-Leitlinie) - PSMA-Liganden-PET/CT in der Diagnostik des Prostatakarzinoms - Stand: 01/2022 - AWMF-Registernummer: 031-055 - Afshar-Oromieh, Ali; Eiber, Matthias; Fendler, Wolfgang; Schmidt, Matthias; Rahbar, Kambiz; Ahmadzadehfar, Hojjat; Umutlu, Lale; Hadaschik, Boris; Hakenberg, Oliver W.; Fornara, Paolo; Kurth, Jens; Neels, O.; et al. (Nuklearmedizin, 2023)
PSMA-PET/CT for imaging prostate cancer (PC) has spread worldwide since its clinical introduction in 2011. The majority of experiences have been collected for PSMA-PET-imaging of recurrent PC. Data for primary staging of high-risk PC are highly promising. Meanwhile, a plethora of PSMA-ligands are available for clinical use (e.g. 68Ga-PSMA-11, 68Ga-PSMA-I&T, 68Ga-PSMA-617, 18F-DCFBC, 18F-DCFPyL, 18F-PSMA-1007, 18F-rhPSMA-7 and 18F-JK-PSMA-7). However, an official approval is available only for 68Ga-PSMA-11 (approved by the US FDA in 2020) and 18F-DCFPyL (approved by the US FDA in 2021). Recommendations for acquisition times vary from 1–2h p.i. It has been shown that for the majority of tumour lesions, the contrast in PSMA-PET/CT increases with time. Therefore, additional late imaging can help to clarify unclear findings. PSMA-PET/CT should be performed prior to commencing an androgen deprivation therapy (ADT) since (long term) ADT reduces the visibility of PC lesions. Following injection of PSMA-ligands, hydration and forced diuresis are recommended for PSMA-ligands with primarily excretion via the kidneys in order to increase the visibility of tumour lesions adjacent to the urinary bladder.PSMA-ligands are physiologically taken up in multiple normal organs. For some 18F-labelled PSMA-ligands, presence of unspecific focal bone uptake has been reported. When using these tracers, focal bone uptake without CT-correlate should be interpreted with great caution. Besides prostate cancer, practically all solid tumors express PSMA in their neovasculature thereby taking up PSMA-ligands, although usually at a lower extent compared to PC. Also multiple benign lesions and inflammatory processes (e.g. lymph nodes) take up PSMA-ligands, also usually at lower extent compared to PC.
Gesehen am 22.03.2023